Phytochemical Composition, Antioxidant, and Antibacterial Potential of Tridax procumbens Plant Fraction from West Sumatera, Indonesia: Phytochemical Composition, Antioxidant, and Antibacterial Potential of Tridax procumbens - Widyawati; Situmeang, Boima (Journal of Tropical Life Science, 2026)
Research on the Gletang plant (Tridax procumbens) is still in its nascent stages and requires further development. The presence of secondary metabolites such as alkaloids, flavonoids, phenolics, terpenoids, and tannins is one of the reasons for the potential possessed by T. procumbens. Our previous study successfully demonstrated the antibacterial activity of leaf, flower, and stem extracts against oral pathogenic bacteria, specifically Streptococcus mutans and Enterococcus faecalis. This study introduces a bioactivity guided fractionation approach of Tridax procumbens, integrating phytochemical profiling, antioxidant, and antibacterial evaluations, coupled with LC-MS based compound identification to pinpoint the most active fraction. The fractionation of T. procumbens was carried out using column chromatography. Phytochemical screening tests, total phenolic and total flavonoid content analyses, antioxidant activity and antibacterial activity test were conducted for all fractions. The EATF was found to have the highest total flavonoid content (TFC) and total phenolic content (TPC), with mean values of 16.573 ± 0.04 mg QE/g and 10.993 ± 0.05 mg GAE/g, respectively. The highest antioxidant activity was also found in EATP with an IC50 of 5.839 ± 0.100 ppm. Antibacterial activity revealed that the EATP exhibited the best antibacterial activity against S. mutans and E. faecalis. The LC-MS analysis indicated the presence of octaverine, myristyl myristate, phenol, 2,2'-methylenebis(3,5,6-trichloro), and β-carotene in EATP. The findings provide a scientific basis for the development of plant based antibacterial agents targeting oral pathogens, while also supporting the advancement of evidence based phytopharmaceutical applications.